Produção de carne bovina orgânica: Uma avaliação dos impactos socioeconômicos na região do pantanal do Brasil - Neves, Daniel Almeida Lopes; Soares, João Paulo Guimarães [UNESP]; Carvalho, José Márcio [UNESP] (Centro Universitario de Maringa, 2016)
The social impacts of agro-ecological transition from the production of conventional beef to organic beef are evaluated in Brazilian production units, by the Ambitec method developed by the Embrapa Meio Ambiente. Nine production units were evaluated in the state of Mato Grosso do Sul, Brazil. They integrated the only 18 Brazilian producers of organic beef. Data were collected in the second trimester of 2012 by questionnaires applied to representatives of farms who attributed a mark which represents alteration provided by the systems' agro-ecological transition, to each variable analyzed. After inserting the alteration coefficients of each variable of indicators per production unit, impact coefficient was immediately calculated by an Ambitec sheet. When compared to the conventional one, the organic management of production provided positive social impact, with the highest contributions provided by the positive effects of the following indexes: Capacity (μ = 9.69), generation of earnings (μ = 13.75), Dedication and Profile of the Agent (μ = 12.86) and Institutional Relationship (μ = 12.19). In the case of grouping analysis, producers 1, 6 and 7 had the highest average in the general index of social impact of organic production (μ = 6.83). KEY WORDS: Agro-Ecology; Organic Beef; Employment; Earnings; Health; Sustainability.
Production of organic beef: Evaluation of the socioeconomic impacts on the Brazilian Pantanal Region